Automatic Segmentation and Quantification of Nigrosome‐1 Neuromelanin and Iron in MRI: A Candidate Biomarker for Parkinson's Disease - Ariz, Mikel; Martínez, Martín; Alvarez, Ignacio; Fernández‐Seara, Maria A.; Castellanos, Gabriel; Pastor, Pau; Pastor, Maria A.; Ortiz de Solórzano, Carlos (Journal of magnetic resonance imaging, 2024)
Background There is a lack of automated tools for the segmentation and quantification of neuromelanin (NM) and iron in the nigrosome‐1 (N1). Existing tools evaluate the N1 sign, i.e., the presence or absence of the “swallow‐tail” in iron‐sensitive MRI, or globally analyze the MRI signal in an area containing the N1, without providing a volumetric delineation. Purpose Present an automated method to segment the N1 and quantify differences in N1's NM and iron content between Parkinson's disease (PD) patients and healthy controls (HCs). Study whether N1 degeneration is clinically related to PD and could be used as a biomarker of the disease. Study Type Prospective. Subjects Seventy‐one PD (65.3 ± 10.3 years old, 34 female/37 male); 30 HC (62.7 ± 7.8 years old, 17 female/13 male). Field Strength/Sequence 3 T Anatomical T1‐weighted MPRAGE, NM‐MRI T1‐weighted gradient with magnetization transfer, susceptibility‐weighted imaging (SWI). Assessment N1 was automatically segmented in SWI images using a multi‐image atlas, populated with healthy N1 structures manually annotated by a neurologist. Relative NM and iron content were quantified and their diagnostic performance assessed and compared with the substantia nigra pars compacta (SNc). The association between image parameters and clinically relevant variables was studied. Statistical Tests Nonparametric tests were used (Mann–Whitney's U, chi‐square, and Friedman tests) at P = 0.05. Results N1's relative NM content decreased and relative iron content increased in PD patients compared with HCs (NM‐CRHC = 22.55 ± 1.49; NM‐CRPD = 19.79 ± 1.92; NM‐nVolHC = 2.69 × 10−5 ± 1.02 × 10−5; NM‐nVolPD = 1.18 × 10−5 ± 0.96 × 10−5; Iron‐CRHC = 10.51 ± 2.64; Iron‐CRPD = 19.35 ± 7.88; Iron‐nVolHC = 0.72 × 10−5 ± 0.81 × 10−5; Iron‐nVolPD = 2.82 × 10−5 ± 2.04 × 10−5). Binary logistic regression analyses combining N1 and SNc image parameters yielded a top AUC = 0.955. Significant correlation was found between most N1 parameters and both disease duration (ρNM‐CR = −0.31; ρiron‐CR = 0.43; ρiron‐nVol = 0.46) and the motor status (ρNM‐nVol = −0.27; ρiron‐CR = 0.33; ρiron‐nVol = 0.28), suggesting NM reduction along with iron accumulation in N1 as the disease progresses. Data Conclusion This method provides a fully automatic N1 segmentation, and the analyses performed reveal that N1 relative NM and iron quantification improves diagnostic performance and suggest a relative NM reduction along with a relative iron accumulation in N1 as the disease progresses. Evidence Level 1 Technical Efficacy Stage 1